2012
DOI: 10.1177/0739456x12449483
|View full text |Cite
|
Sign up to set email alerts
|

Is Integrated Planning Any More Than the Sum of Its Parts?

Abstract: Policy integration is currently cresting a wave of interest, with new legal frameworks, programs, and processes emerging. Does integrated sustainability planning, to take one key motivator of this interest in integration, offer more than environmental planning, climate change planning, or other sectoral moves? This article reviews planning research and practice in integration in the context of diverse aspirations for sustainability. Normative claims, central to environmental policy integration, are seldom dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…What is the usability of these planning instruments as perceived by their developers? To provide an answer to these questions, the paper draws on the outcomes of , accessibility analysis and instruments offer a highly suitable framework to support the development of combined land-use and transport strategies, so as to achieve the coordination and synergy required to attain city sustainability goals (Holden 2012;Stead, Geerlings, and Meijers 2004). Indeed, a focus on accessibility makes the overall goal of the land-use and transport system explicit and offers a direct link between the characteristics of flows (i.e., speeds and travel time) and the characteristic of places (i.e., the number of relevant activities in a given area).…”
mentioning
confidence: 99%
“…What is the usability of these planning instruments as perceived by their developers? To provide an answer to these questions, the paper draws on the outcomes of , accessibility analysis and instruments offer a highly suitable framework to support the development of combined land-use and transport strategies, so as to achieve the coordination and synergy required to attain city sustainability goals (Holden 2012;Stead, Geerlings, and Meijers 2004). Indeed, a focus on accessibility makes the overall goal of the land-use and transport system explicit and offers a direct link between the characteristics of flows (i.e., speeds and travel time) and the characteristic of places (i.e., the number of relevant activities in a given area).…”
mentioning
confidence: 99%
“…In order to understand the reasons behind effective implementation of sustainable mobility we need to go beyond the actual measures, and analyse such matters as steering cultures. The paper thus contributes to the understanding of how long-term integration goals connect to short-term actions in planning and decision-making praxis, a research need identified, for example, by Holden (2012).…”
Section: Introductionmentioning
confidence: 99%
“…Creating coherent and consistent urban policy that promotes health, liveability and sustainability requires effective partnerships and collaboration between and within all three levels of government, and with the private and community sectors (Rayner & Howlett, 2009;Holden, 2012). In Australia, policies around land use, social services, health care and transport planning are primarily the responsibility of state governments, with local governments and the community sector focusing on service delivery.…”
Section: Introductionmentioning
confidence: 99%